Micro-structural analysis of cement composites using stone waste: A review. Issue 1 (1st October 2022) - Devi, K; Saini, B; Aggarwal, P
Abstract: The direct disposal of industrial by-products to environment is the potential threat to the ecosystem. A possible solution can be utilization of these materials into construction industries to counteract the consumption of cement. Along with the strength and durability properties, study of micro-structural properties of concrete is equally important. The microstructure of concrete largely depends on the type of cement, admixtures, water-cement ratio and curing age. To characterize and quantify the hydration products i.e., calcium silicate hydrate, calcium hydroxide etc. of cement based materials, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD) etc. techniques are being used worldwide. XRD is a powerful tool for the identification of chemical compounds present in the cement-based materials. SEM reveals the information about external morphology, chemical composition, crystalline structure and orientation of the material. EDS is an analytical technique that can be coupled with SEM and used to determine the elemental composition. A critical review of microstructural analysis using above mentioned techniques for mortar and concrete using stone waste has been done. It was found that these techniques are capable to address the morphological and crystalline structure along with chemical elements and compounds of the materials; and can also be correlated with strength and durability properties. The micrographs showed stone waste, being a filler material aid in forming the dense matrix by filling the voids. Elemental analysis coheres to the chemical compounds (calcium oxide, silica dioxide, etc.) present in the mortar and concrete specimens corresponding to micrographs images.